Safety and Effectiveness of a Perturbation-based Neuromuscular Training Program on Dynamic Balance in Adolescent Females: A Randomized Controlled Trial - Alison Bulow; Judith E Anderson; Jeff R S Leiter; Peter B MacDonald; Jason D Peeler (International Journal of Sports Physical Therapy)
# Background Adolescent females are at much greater risk for ACL injury than their male counterparts when participating in the same sports. Preventative and pre-operative rehabilitation neuromuscular (NM) exercise programs are often recommended to improve knee function and reduce injury rates. The effectiveness of perturbation-based NM training program has been established in an adult population but has yet to be investigated in the at-risk adolescent female population.